Penerapan Metode Question Student Have Untuk Meningkatkan Aktivitas Belajar Peserta Didik - Nurhaswinda Nurhaswinda (el-Ibtidaiy:Journal of Primary Education, 2021)
The background this research is the low learning activity of students, especially in questioning skills in the learning process. This study aims to determine whether there is an increase in the learning activities of students after applying the question student have method. This research is a Classroom Action Research (CAR). The sample of this research was the fourth grade students of the 2018/2019 academic year with 20 students. This research was completed in 2 cycles consisting of four stages, namely planning, acting, observing, and reflecting. The data collection instruments used were observation and documentation. The results showed that using the question student have method can improve the learning activities of students in mathematics in fourth grade of Elementary School Pahlawan. The activity level of students before the question student have method was applied was 54.28% in the low category. After applying the question student have method in Cycle I, there was an increase of 61.07% in the middle category, and in Cycle II there was an increase of 80.72% in the high category. Based on the results of this study, it can be concluded that the application of the question student have method can improve the learning activities of students in mathematics.